Sustained high HIV case‐finding through index testing and partner notification services: experiences from three provinces in Zimbabwe. (19th July 2019) - Mahachi, Nyikadzino; Muchedzi, Auxilia; Tafuma, Taurayi A; Mawora, Peter; Kariuki, Liz; Semo, Bazghina‐werq; Bateganya, Moses H; Nyagura, Tendai; Ncube, Getrude; Merrigan, Mike B; Chabikuli, Otto N; Mpofu, Mulamuli
Abstract: Introduction: Several countries in southern Africa have made significant progress towards reaching the Joint United Nations Programme on HIV/AIDS goal of ensuring that 90% of people living with HIV are aware of their status. In Zimbabwe, progress towards this "first 90" was estimated at 73% in 2016. To reach the remaining people living with HIV who have undiagnosed infection, the Zimbabwe Ministry of Health and Child Care has been promoting index testing and partner notification services (PNS). We describe the implementation of index testing and PNS under the Zimbabwe HIV Care and Treatment (ZHCT) project and the resulting uptake, HIV positivity rate and links to HIV treatment. Methods: The ZHCT project has been implemented since March 2016, covering a total of 12 districts in three provinces. To assess the project's performance on index testing, we extracted data on HIV testing from the district health information system (DHIS 2) from March 2016 to May 2018, validated it using service registers and calculated monthly HIV positivity rates using Microsoft Excel. Data were disaggregated by district, province, sex and service delivery point. We used SPSS to assess for statistical differences in paired monthly HIV positivity rates by sex, testing site, and province. Results: The average HIV positivity rate rose from 10% during the first six months of implementation to more than 30% by August 2016 and was sustained above 30% through May 2018. The overall facility HIV positivity rate was 4.1% during the same period. The high HIV positivity rate was achieved for both males and females (mean monthly HIV positivity rate of 31.3% for males and 33.7% for females), with females showing significantly higher positivity compared to males ( p  < 0.001). The ZHCT mean monthly HIV positivity rate from index testing (32.6%) was significantly higher than that achieved through provider‐initiated testing and counselling and other facility HIV testing modalities (4.1%, p  < 0.001). Conclusions: The ZHCT project has demonstrated successes in implementing index testing and PNS by attaining a high HIV positivity rate sustained over the study period. As the country moves towards HIV epidemic control, index testing and PNS are critical strategies for targeted HIV case identification.